Optimization of the agricultural land structure as the basis of sustainable development of rural areas - Dorosh, Y.; Barvinskyi, A.; Kupriyanchyk, I.; Kravchenko, O.; Saliuta, V. (Land Management, Cadastre and Land Monitoring, 2020)
The modern structure of agricultural lands, formed in the conditions of a radical reformation of land relations in rural areas, is analyzed. It is revealed that this structure in agricultural enterprises of different forms of ownership does not meet the principles of rational use of nature due to the excessive share of arable land and low - environmentally sustainable land. At the same time, the share of the arable land in the structure of agricultural land in the non-state agricultural enterprises is 11-12% higher than in the state-owned, which is explained by the efforts of private entrepreneurs – tenants aimed at increasing agricultural production by expanding the area of arable land. The extremely high level of plowing of agricultural land is a consequence of the extensive use of land resources and the main reason for the spread of degradation processes. The only solution to this problem is the development of land management projects that provide ecological and economic justification for crop rotation and land management. It is shown that the sustainable development of rural territories is not possible without improvement of the structure of sown areas, the main current disadvantage of which is the market-driven excessive share of highly profitable crops of the technical group and a very low share of forage crops, which can be the cause not only of the ecological but also of the socio-economic problems. Optimization of the structure of the sown areas of crops should be carried out on the basis of ecological-landscape land management in consideration with the soil and climatic conditions of specific rural territories and resource provision of agricultural enterprises. Key words: agricultural land, structure of cultivation ares, agrarian enterprises, organization of territory, crop rotation.